The Testing Of Pecking Order Theory For Behavior Financing In The Company's Life Stage - Ode Sumail; Rezky Arianty Akob (University of Merdeka Malang, 2022)
The diversity of behavior financing occurs in companies listed on the Indonesian capital market and still leaves debate on theoretical assumptions so that the researchers are motivated to do this research. This research aims to investigate the behavior financing of each stage of the company's life, specifically for young, mature and waning ages as the repressentations of Pecking Order Theory (POT) financing behavior. The object of this research is a manufacturing company that is listed Indonesian capital market at least 3 years after the IPO and has a complete financial performance report. The results of the regression analysis results behavior of sales growth, profitability behavior, dividend behavior, retained earnings behavior, free cash flow behavior, risk behavior, size behavior and financial leverage behavior, shows various behaviors in each stage of the company's life. Behavior financing at the young and waning stages tends to favorPOTbehavior rather than trade-off behavior financing. In the mature stage, the behavior of profitability, retained earnings,FCF, and size do not supportPOTbehavior tends to lead to trade-off financing behavior.